CCR10/CCL27 crosstalk contributes to failure of proteasome-inhibitors in multiple myeloma - Thangavadivel, Shanmugapriya; Zelle-Rieser, Claudia; Olivier, Angelika; Postert, Benno; Untergasser, Gerold; Kern, Johann; Brunner, Andrea; Gunsilius, Eberhard; Biedermann, Rainer; Hajek, Roman; Pour, Ludek; Willenbacher, Wolfgang; et al. (Oncotarget, 2016)
The bone marrow microenvironment plays a decisive role in multiple myeloma progression and drug resistance. Chemokines are soluble mediators of cell migration, proliferation and survival and essentially modulate tumor progression and drug resistance. Here we investigated bone marrow-derived chemokines of naive and therapy-refractory myeloma patients and discovered that high levels of the chemokine CCL27, known so far for its role in skin inflammatory processes, correlated with worse overall survival of the patients. In addition, chemokine levels were significantly higher in samples from patients who became refractory to bortezomib at first line treatment compared to resistance at later treatment lines.In vitro as well as in an in vivo model we could show that CCL27 triggers bortezomib-resistance of myeloma cells. This effect was strictly dependent on the expression of the respective receptor, CCR10, on stroma cells and involved the modulation of IL-10 expression, activation of myeloma survival pathways, and modulation of proteasomal activity. Drug resistance could be totally reversed by blocking CCR10 by siRNA as well as blocking IL-10 and its receptor.From our data we suggest that blocking the CCR10/CCL27/IL-10 myeloma-stroma crosstalk is a novel therapeutic target that could be especially relevant in early refractory myeloma patients.
Keywords: senioři; Tumor Microenvironment; nádorové buněčné linie; signální transdukce; Xenograft Model Antitumor Assays; Cell Movement; nádorové mikroprostředí; drug resistance; apoptóza; Multiple Myeloma; Receptors, CCR10; transfekce; receptory interleukinu-10; RNA interference; Bortezomib; Middle Aged; Proteasome Endopeptidase Complex; mužské pohlaví; Proteasome Inhibitors; Signal Transduction; Receptor Cross-Talk; CCL27; interleukin-10; RNA Interference; Cell Proliferation; Cell Line, Tumor; proteasomový endopeptidasový komplex; stroma cells; myeloma; chemorezistence; mnohočetný myelom; Chemokine CCL27; interakce mezi receptory a ligandy; ženské pohlaví; xenogenní modely - testy protinádorové aktivity; bortezomib; Humans; inhibitory proteasomu; Drug Resistance, Neoplasm; pohyb buněk; CCR10; lidé středního věku; Transfection; receptory CCR10; proliferace buněk; Interleukin-10; Female; Aged; chemokin CCL27; Receptors, Interleukin-10; lidé; Male; Apoptosis